Characterization of a Mr = 56,000 polypeptide associated with 10S DNA polymerase alpha purified from calf thymus using monoclonal antibody. - Masaki, S (1985)
Existence of a Mr = 56,000 polypeptide associated with 10S DNA polymerase alpha was shown by production of a monoclonal anti-calf thymus 10S DNA polymerase alpha antibody secreted from a hybridoma line named 3H1. The antibody bound three polypeptides with Mr = 180,000, 56,000 and 32,000 in hydroxylapatite fraction of 10S DNA polymerase alpha by immunoblot. The antibody co-precipitated the polypeptides with the large polypeptide (Mr = 150,000-140,000) of 10S DNA polymerase alpha with the aid of second antibody. Among three polypeptides, the Mr = 56,000 polypeptide was co-purified with DNA polymerase alpha through DNA-cellulose chromatography and repeated sucrose rate-zonal centrifugations. The Mr = 56,000 polypeptide was still associated with 10S DNA polymerase alpha after second sucrose rate-zonal centrifugation, but the amount of it was reduced. The polypeptide was banded at pH 7.2-8.0 and displayed microheterogeneity in respect of isoelectric point by isoelectrofocusing with 7 M urea, and showed weak DNA-binding property after blotting onto a nitrocellulose. The antibody against the polypeptide precipitated DNA polymerase alpha from human, rat, and mouse, and Mr = 56,000 and 32,000 polypeptides were detected in these DNA polymerase alpha fractions by immunoblot. These results suggest that the polypeptide with Mr = 56,000 may take part in the DNA polymerase reaction.